2014
DOI: 10.1136/bmjopen-2013-004516
|View full text |Cite
|
Sign up to set email alerts
|

Non-cancer morbidity among Estonian Chernobyl cleanup workers: a register-based cohort study

Abstract: ObjectiveTo examine non-cancer morbidity in the Estonian Chernobyl cleanup workers cohort compared with the population sample with special attention to radiation-related diseases and mental health disorders.DesignRegister-based cohort study.SettingEstonia.ParticipantsAn exposed cohort of 3680 men (cleanup workers) and an unexposed cohort of 7631 men (population sample) were followed from 2004 to 2012 through the Population Registry and Health Insurance Fund database.MethodsMorbidity in the exposed cohort compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 42 publications
6
26
1
Order By: Relevance
“…Strikingly, 24 years later, these men, at an average age of 55, continued to have significantly more depressive and anxiety symptoms than controls, and were less likely to be employed and married and to describe their overall health as good. These findings complement and extend prior studies of Chernobyl clean-up workers that showed an increase in non-radiation related physical morbidity [ 2 ], PTSD, depression, and work absenteeism [ 3 ], and suicide [ 4 ]. Local Ukrainian studies have also raised the possibility of neurocognitive and brain-related impairments in highly exposed workers (reviewed in [ 5 ]).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Strikingly, 24 years later, these men, at an average age of 55, continued to have significantly more depressive and anxiety symptoms than controls, and were less likely to be employed and married and to describe their overall health as good. These findings complement and extend prior studies of Chernobyl clean-up workers that showed an increase in non-radiation related physical morbidity [ 2 ], PTSD, depression, and work absenteeism [ 3 ], and suicide [ 4 ]. Local Ukrainian studies have also raised the possibility of neurocognitive and brain-related impairments in highly exposed workers (reviewed in [ 5 ]).…”
Section: Introductionsupporting
confidence: 87%
“…Most samples of workers studied after toxic disasters are volunteers or individuals who self-enroll in monitoring programs [ 9 ]. There are exceptions, such as the WTC firefighters whose jobs require annual examinations and the Registry-based studies of Estonian clean-up workers [ 2 , 4 ]. The limitations to generalizing from volunteer and monitoring samples are obvious [ 9 ].…”
Section: Some Methodological Challengesmentioning
confidence: 99%
“…There is an urgent need for interventions by non-specialist workers that can address a range of mental health problems 3 . The World Health Organization (WHO)'s Problem Management Plus (PM1) is a brief transdiagnostic psychological intervention employing evidence-based strategies of problem solving, behavioural activation, strengthening social support, and stress management 4 . We adapted the individual treatment format of this intervention for conflict-affected Peshawar in Pakistan.…”
Section: Problem Management Plus (Pm1): Pilot Trial Of a Who Transdiamentioning
confidence: 99%
“…Rather, recent publications are based on data obtained prior to 2011. The exception is a health registry study in Tallinn, Estonia, that found an increase in clinical diagnoses of nervous system disorders and intentional self-harm in liquidators compared to controls 4 . Other recently published research on liquidators includes a survey from Tallinn that confirmed findings from Ukraine about elevated rates of common mental disorders and suicidal ideation 5 , and papers on neurocognitive abnormalities in Ukrainian liquidators 6 .…”
mentioning
confidence: 99%
“…Although currently it has been suggested the threshold level of radiation exposure dose related with cardiovascular disease might be lower than estimated previously, 21 non-cancer diseases, the ‘deterministic health effect,’ is known to exist within certain threshold exposure doses. 22 Therefore, it is difficult to interpret the significant association between self-reported hypertension and hyperlipidemia in females with estimated radiation dose in the present study. The reason might be due to unknown confounding effects that we could not consider, something with an unknown biological mechanism, reporting bias that could not be assessed in the cross-sectional design, or residual cofounding effect of age in which the higher exposed respondents have a higher age than the lower exposed respondents in the present study ( Supplementary Table 2 ).…”
Section: Discussionmentioning
confidence: 69%